Right To Be Forgotten as an Effort to Suppress Recidivism Rate of Theft Crime - Dian Rachmat Gumelar; Andhiya Moza Faris (Fakultas Hukum Universitas Muhammadiyah Sorong, 2024)
This research’s background is from the thievery recidivist cases that appear frequently. The recidivist case itself, as the general public has known for a long time, is caused by various factors, one of them being an economic factor. This differs from state officials’ corruption cases that did not have any correlation with the economic condition of the defendants. The aim of this research is to prove that the Right to Be Forgotten can be a solution for decreasing the number of thievery recidivist criminal acts in In the current digital era, there is a close connection with digital footprints, making job opportunities for theft ex-convicts limited. This aspect is then one of the main focuses of the study. This article uses the normative juridical as a research method by utilizing relevant literature from other journal articles, books, and related documents. The results of the research’s is that to support the new penal system where the rehabilitative and the humanism aspects are being highlighted, the act of “clearing name” for ex-convicts is needed to support them to have more job options after they get out of the prison other than owning a Small and Medium Enterprise (SMEs) with the skills they got when they were in the prison. The reason for that is with the development of technology, one of the indicators for hiring someone is to watch out for their record, both on the internet and social media.